2017
DOI: 10.5606/archrheumatol.2017.6028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fibromyalgia Syndrome on Physical Function and Psychological Status of Pregnant Females

Abstract: Objectives: This study aims to investigate the frequency and most common symptoms of fibromyalgia syndrome (FS) among pregnant females and determine the impacts of FS on physical functioning and psychological status. Patients and methods: A total of 360 pregnant females (mean age 26.5 years, range 19 to 42 years) were included. The subjects were divided into two groups in terms of having (FS group; n=136; mean age 27 years; range 19 to 41 years) or not having FS (control group; n=224; mean age 26.5 years; rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The P12 program had initially been created under the assumption that a less intensive program is more suitable for patients suffering from fibromyalgia, as it has previously been shown that fibromyalgia patients have limited physical resources. [ 26 , 27 ] Our results can thus encourage healthcare providers to offer a more intensive therapy.…”
Section: Discussionmentioning
confidence: 77%
“…The P12 program had initially been created under the assumption that a less intensive program is more suitable for patients suffering from fibromyalgia, as it has previously been shown that fibromyalgia patients have limited physical resources. [ 26 , 27 ] Our results can thus encourage healthcare providers to offer a more intensive therapy.…”
Section: Discussionmentioning
confidence: 77%
“…However, these studies did not confirm whether any of these patients had pre-existing FM. Other studies demonstrated that pregnant females with pre-existing FM experienced an aggravation of symptoms throughout pregnancy, and particularly in the third trimester, the symptoms were at their worst [46][47][48]. There were also reported changes to symptoms in the postnatal period, while hormonal changes connected with abortion, use of hormonal contraceptives, and breastfeeding did not modulate FM symptom severity [45,49,50].…”
Section: Interactions Between Fm and Pregnancymentioning
confidence: 97%